Peran Protektor Vitamin D Dalam Mempertahankan Massa Otot Pada Kelompok Lanjut Usia - Ernawati Ernawati; Frisca Frisca; Alexander Halim Santoso; Edwin Destra; Farell Christian Gunaidi; Alicia Herdiman; Friliesa Averina (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The increase in the global elderly population increases the risk of sarkopenia, which can reduce activity capacity. Vitamin D deficiency is common in the elderly and plays an important role in musculoskeletal function. This study aims to evaluate the relationship between vitamin D levels and the incidence of sarcopenia in the elderly. This cross-sectional study with a total sampling method involved 93 elderly people aged ≥ 60 years who lived at the Bina Bhakti Nursing Home. Measurements were made on serum vitamin D levels, mid upper arm circumference and calf circumference. Spearman correlation analysis was used to evaluate the relationship between these variables. The results showed that the mean mid upper arm circumference was 23.61 cm (SD = 5.02) with a median of 23 cm, while the mean calf circumference was 28.72 cm (SD = 5.15) with a median of 29 cm. The mean serum vitamin D level was 9.78 ng/mL (SD = 4.47) with a median of 7.5 ng/mL. Spearman correlation analysis showed a significant relationship between mid upper arm circumference and calf circumference (r = 0.572; p 0.01), upper arm circumference and vitamin D levels (r = 0.254; p = 0.014), and calf circumference and vitamin D levels ( r = 0.218; p = 0.036). This research shows that there is a significant relationship between vitamin D levels and upper arm and calf circumference in the elderly. Vitamin D deficiency is common in the elderly and plays an important role in the prevention and treatment of sarcopenia. Further research is needed to understand the role of vitamin D in preventing muscle loss. Keywords: Calf Circumference, Mid Upper Arm Circumference, Sarkopenia, Vitamin D.  ABSTRAK Peningkatan populasi lanjut usia global meningkatkan risiko sarkopenia, yang dapat mengurangi kemampuan aktivitas. Kekurangan vitamin D umum terjadi pada lansia dan berperan penting dalam fungsi muskuloskeletal. Penelitian ini bertujuan untuk mengevaluasi hubungan kadar vitamin D dengan kejadian sarkopenia pada lansia. Penelitian ini menggunakan desain potong lintang dengan metode pengambilan sampel total dengan melibatkan 93 lansia berusia ≥ 60 tahun yang tinggal di Panti Werdha Bina Bhakti. Pengukuran dilakukan terhadap kadar vitamin D serum, lingkar lengan atas, dan lingkar betis. Analisis korelasi Spearman digunakan untuk mengevaluasi hubungan antara variabel-variabel tersebut. Hasil penelitian menunjukkan bahwa rerata lingkar lengan atas adalah 23,61 cm (SD = 5,02) dengan median 23 cm, sedangkan rerata lingkar betis adalah 28,72 cm (SD = 5,15) dengan median 29 cm. Rerata kadar vitamin D serum adalah 9,78 ng/mL (SD = 4,47) dengan median 7,5 ng/mL. Analisis korelasi Spearman menunjukkan hubungan signifikan antara lingkar lengan atas dan lingkar betis (r = 0,572; p  0,01), lingkar lengan atas dengan kadar vitamin D (r = 0,254; p = 0,014), serta lingkar betis dengan kadar vitamin D (r = 0,218; p = 0,036). Penelitian ini menunjukkan bahwa terdapat hubungan signifikan antara kadar vitamin D dengan lingkar lengan atas dan betis pada lansia. Kekurangan vitamin D umum terjadi pada lansia dan berperan penting dalam pencegahan dan pengobatan sarkopenia. Penelitian lebih lanjut diperlukan untuk memahami peran vitamin D dalam pencegahan penurunan massa otot. Kata Kunci: Lingkar Betis, Lingkar Lengan Atas, Sarkopenia, Vitamin D.